Assessment of the impact of outdoor activities at leisure facilities on the physical activity of 15-year-old schoolchildren during the COVID-19 pandemic - OLENA ANDRIEIEVA; TARAS BLYSTIV; NATALIIA BYSHEVETS; YURIY MOSEYCHUK; LARISA BALATSKA; TATIANA LIASOTA; ANDRIY BRAZHANYUK; ANTONINA BOHDANYUK (Journal of Physical Education and Sport, 2022)
Abstract Introduction. Given the steady decline in physical activity among all categories of Ukrainian citizens, due to quarantine restrictions caused by the Covid-19 pandemic, there is a threatening trend of declining levels of their physical health. In the last period of time, the world has undergone significant changes, namely the emergence of the Covid-19 virus, which has altered human life. During the pandemic Covid-19, fitness is essential in preventing physical and mental health problems among schoolchildren. This requires the development of preventive measures aimed at increasing the body's resistance to disease. Material and methods. The study was conducted on the basis of the Municipal Institution in the Lviv Regional Council “Lviv Regional Center for Local Lore, Excursions and Tourism of Student Youth”. 51 students participated in the experiment, including 32 boys and 19 girls aged 15. Drawing on their health condition, they were allocated to main medical group. The group of experts included 27 qualified specialists familiar with the issues of children's and youth tourism and physical education. The following methods were used during the research: study, systematization and generalization of literature and best pedagogical experience, expert assessment method, anthropometric, physiological research methods, pedagogical testing, Framingham method of motor activity assessment, methods of mathematical statistics. Results. Among the programmes aimed at high school students, their health and recreation in the framework of out-of-school educational institutions, comprehensive programmes that include lessons of theoretical and practical nature are the most effective. Thus, we offered the programme based on walking tourism. It was aimed at high school students and was introduced within the framework of the out-ofschool educational institutions of tourism and local lore. The study proves the changes in the daily activities of adolescents regardless of gender. Comparing to the beginning of the experiment in the structure of their daily motor activity the time spent on a sedentary level has significantly (p<0.05) decreased at the end of the experiemnt. In addition, in all groups the volume of motor activity of medium and high levels statistically (p<0.05) increased. There were positive changes in the indicators of the cardiovascular and respiratory systems, indicators of physical health and fitness. Conclusions. The obtained results testify to the effectiveness of the proposed programme of lessons based on walking tourism with 15-year-old students within the framework of out-of-school educational institutions of tourism and local lore. Therefore, the proposed programme should be included in the organizational and methodological support of health and recreational activities in educational institutions as a part of extracurricular activities focused on tourism and local lore.
Keywords: pandemic, efficiency, high school students, health and recreation activities, walking tourism